2004
DOI: 10.1073/pnas.0404458101
|View full text |Cite
|
Sign up to set email alerts
|

A nontransgenic mouse model shows inducible amyloid-β (Aβ) peptide deposition and elucidates the role of apolipoprotein E in the amyloid cascade

Abstract: The amyloid-␤ (A␤) peptide, a major pathological hallmark of Alzheimer's disease (AD), undergoes a cascade of interactions resulting in the formation of soluble aggregates and their conversion in the brain to insoluble deposits and mature senile plaques. Furthermore, the apoE4 isoform of apolipoprotein E (apoE), which is the major genetic risk factor of AD, is associated with increased A␤ deposition. It is not known how the different A␤ aggregates in the amyloid cascade are formed, contribute to the pathogenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
65
1
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(72 citation statements)
references
References 55 publications
5
65
1
1
Order By: Relevance
“…Recently endogenous murine A␤ was reported to have a crucial role in synaptic activity (35), and endogenous murine A␤ oligomers suggested a role regulating synaptic activity. Moreover, by the prolonged inhibition of A␤-degrading enzyme neprilysin in the brain of wild-type mice, it has been reported that murine A␤ is deposited in the brain (36), suggesting that murine A␤ may undergo a process of oligomerization and fibrillization similar to human A␤.…”
Section: Discussionmentioning
confidence: 99%
“…Recently endogenous murine A␤ was reported to have a crucial role in synaptic activity (35), and endogenous murine A␤ oligomers suggested a role regulating synaptic activity. Moreover, by the prolonged inhibition of A␤-degrading enzyme neprilysin in the brain of wild-type mice, it has been reported that murine A␤ is deposited in the brain (36), suggesting that murine A␤ may undergo a process of oligomerization and fibrillization similar to human A␤.…”
Section: Discussionmentioning
confidence: 99%
“…In postmortem AD brain sections, apoE4 is associated with greater A deposition, amyloid dye reactivity, and density of neuritic plaques than apoE3 12 . Transgenic mouse models of AD also show that apoE is central to influencing A amyloid plaque pathology and deposition 6,11 . Older transgenic mice expressing the V717F mutant of amyloid precursor protein (APP) develop significantly greater quantities of thioflavin-S-reactive neuritic plaques in the hippocampus when also expressing human apoE in astrocytes under the glial fibrillary acidic protein (GFAP) promoter 6 .…”
Section: Introductionmentioning
confidence: 99%
“…A and mediation of fibrillization and plaque formation, the binding and disruption of membranes by apoE, apoE-mediated lipid transport, and apoE-mediated neuronal sensitivity to injury and recovery [3][4][5][6][7][8][9][10][11] .…”
Section: Introductionmentioning
confidence: 99%
“…4 However, when treated with thiorphan, an NEP endopeptidase inhibitor, mice and rats demonstrate pathological accumulations of A␤ after only 1 month. 2,5 This was also found in mice treated with phosphoramidon, another NEP inhibitor. 6 These results indicate that there may exist additional NEPlike endopeptidases in the metalloprotease 13 (M13) family that are central to the A␤ clearance pathway.…”
mentioning
confidence: 59%
“…Previous studies have demonstrated that treating rodents with inhibitors of NEP/NEP2 (ie, phosphoramidon and thiorphan) produces more dramatic elevations in A␤ (30-to 50-fold). 2,5,6 However, despite the lack of both NEP and NEP2 genes, only modest elevations in A␤ peptides were observed in our double-knockout studies-well below known plaque-inducing levels. As expected, the immunohistochemical analysis of 14-month-old DKO mice did not show evidence of plaque deposition (data not shown).…”
Section: Discussionmentioning
confidence: 91%